2000
DOI: 10.1128/iai.68.8.4470-4476.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity againstListeria monocytogenesin the Absence of Type I Tumor Necrosis Factor Receptor p55

Abstract: Tumor necrosis factor (TNF) and the type I TNF receptor (TNFRI), p55, are critical for resistance against primary infections with the intracellular bacterial pathogen Listeria monocytogenes. Importantly, however, susceptibility to primary listeriosis in cytokine-deficient mice does not preclude the development or expression of effective adaptive immunity against virulent L. monocytogenes. We used TNFRI ؊/؊ mice to study adaptive antilisterial immunity in the absence of interactions between TNF and TNFRI. Our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This is in line with previous reports showing a critical role of cell-mediated immunity of CD8 T cells in controlling infection. 31,32 To assess whether membraneexpressed TNF on lymphocytes could confer protection, lymphocytes from immunized mice were transferred into TNF Ϫ/Ϫ mice. Splenocytes from mem-TNF mice, but not TNF Ϫ/Ϫ mice, conferred protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous reports showing a critical role of cell-mediated immunity of CD8 T cells in controlling infection. 31,32 To assess whether membraneexpressed TNF on lymphocytes could confer protection, lymphocytes from immunized mice were transferred into TNF Ϫ/Ϫ mice. Splenocytes from mem-TNF mice, but not TNF Ϫ/Ϫ mice, conferred protection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TNF appears not to be required for an antigen-specific immune response, consistent with previous reports. 31,32 We next asked whether membrane TNF expressed on antigen-specific lymphocytes was sufficient to confer effective protection in vivo. To this end, TNF Ϫ/Ϫ mice received splenic lymphocytes (2 ϫ 10 7 cells, 95% lymphocytes) from wild-type, mem-TNF mice, or TNF Ϫ/Ϫ mice, either naïve or preinfected for 7 days with ActA-deficient LM strain (10 6 CFU).…”
Section: T-cell Response To Lm and Protection Of Tnfdeficient Mice Bymentioning
confidence: 99%
“…Surprisingly, neither IFN-+ , TNF- § nor IL-12 is required for the development of a protective CD8 + T cell response [47,[52][53][54]. However, studies in which mice were injected with live bacteria or HKLM strongly supported the idea that innate mechanisms had a strong impact on the quality of the T cell response [36].…”
Section: T Cell Primingmentioning
confidence: 99%
“…Within an infected cell, unipolar expression of ActA by Lm facilitates and is required for bacterium to recruit host cell actin into organized tails, allowing for intracellular spread leading to a productive infection (25). We and others have demonstrated that infection with the ⌬actA Lm mutant is able to prime Lm-specific CD8 and CD4 T cells, and yet is nonlethal even at relatively high inocula (up to 10 6 CFUs) in mice deficient in components of innate immunity such as MyD88, IFN-␥, or TNF-␣ receptor normally essential for protection from WT Lm infection (20,26,27). To verify that the absence of either IL-12 or IFN-IR signaling does not significantly alter the Lm load following infection with Lm-OVA ⌬actA, we examined the number of bacteria in the spleen of IFN-IR Ϫ/Ϫ , IL-12P40 Ϫ/Ϫ , and control mice following infection with 10 6 CFUs of Lm-OVA ⌬actA (Fig.…”
Section: Relative Roles Of Il-12 and Ifn-i Signaling In The Host For mentioning
confidence: 99%